Digital customer as a creator of the reputation of modern companies - Danuta Szwajca (Foundations of Management, 2019)
Scientific and technical developments and progressive digitization in almost all areas of life have led to the development of a new type of digital customer, with specific requirements and expectations for suppliers of goods and services. Customers, in particular consumers, are one of the key groups of stakeholders who create the corporate reputation. Customers are first of all creators of the corporate reputation as an "offeror" and "supplier" of value to buyers, as well as co-creators of the company's reputation as a market player, employer, business partner or citizen, because their purchase decisions determine the company's ability to meet the expectations of other stakeholder groups, that is, investors, employees or business partners. Building and maintaining a good reputation requires proper identification and satisfaction of the needs of key stakeholder groups. The aim of the article is to identify the specific requirements and expectations of digital customers in the context of building and maintaining a good reputation of the company. The thesis is that the digital customer expects, first and foremost, reliability and personalization in their relations with the supplier.
Keywords: L14; L25; M31; 650; digital customer; corporate reputation; reputation management; stakeholders